The Positive and Negative Outcome of Morphine and Disulfiram Subacute Co-Administration in Rats in the Absence of Ethanol Challenge - Karolina Frączek; Agnieszka Kowalczyk; Martyna Pekala; Kaja Kasarello; Grażyna Sygitowicz; Dorota Sulejczak; Malgorzata Zaremba; Marek Konop; Malgorzata Frankowska; Malgorzata Filip; Magdalena Bujalska-Zadrozny; Patrycja Kleczkowska (MDPI AG, 2020)
Recently, a well-known anti-alcohol agent, disulfiram (DSF), has gain much interest, as it was found to be effective in the treatment of cocaine abusers, thus also giving hope for patients addicted to opioids and other illicit drugs. Therefore, this study was aimed to investigate the possible outcome that might occur within the subacute co-administration of both morphine (MRF) and DSF in rats, but in the absence of ethanol challenge. As observed, intraperitoneal DSF dose-dependently enhanced MRF-mediated analgesia with the maximal efficacy at a dose of 100 mg/kg. Furthermore, MRF-induced tolerance and aggressive behavior were significantly reduced by DSF (100 mg/kg, i.p.) in comparison to MRF solely. Nonetheless, significant blood biochemical markers of hepatotoxicity were found (i.e., alteration in the levels of glutathione, blood urea nitrogen, etc.), following a combination of both drugs. Likewise, histological analysis of liver tissue revealed severe changes in the group of DSF + MRF, which includes swelling, cell death, damage to certain vessels, and hemorrhages into the liver parenchyma. Our findings indicate that DSF should be used with extreme caution, especially within the course of subacute concomitant use with MRF, as several possible side effects may take place.